IL-6 as a major regulator of MDSC activity and possible target for cancer immunotherapy - Bitsch, Rebekka; Groth, Christopher; Lasser, Samantha; Arkhypov, Ihor; Petrova, Vera; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor (Cellular immunology, 2021)
Myeloid-derived suppressor cells (MDSC) are generated during tumor progression and suppress the anti-tumor functions of T and natural killer (NK) cells. Their enrichment is associated with a bad prognosis and a worse outcome of immunotherapy in cancer patients. The cytokine interleukin (IL)-6 was found to be a crucial regulator of MDSC accumulation and activation as well as a factor, stimulating tumor cell proliferation, survival, invasiveness and metastasis. Accordingly, IL-6 can serve as a negative prognostic marker in cancer. On the other hand, this cytokine is also involved in T cell activation. This review discusses the pleiotropic effects of IL-6 on immune cell populations that are critical for tumor development, such as MDSC and T cells, and summarizes the data on targeting IL-6 or IL-6 receptor (IL-6R) for tumor immunotherapy to block MDSC-mediated immunosuppression in cancer patients.
Available online 29 November 2020
Gesehen am 08.02.2021